Clinical trial to evaluate immunogenicity and safety of inactivated hepatitis A vaccination starting at 2-month-old children - Kanra, Güler; Yalçın, S. Songül; Ceyhan, Mehmet; Yurdakök, Kadriye (The Turkish Journal of Pediatrics, 2000)
Active immunization with hepatitis A vaccine has been shown to provide long-term protection against hepatitis A virus (HAV) infection. However, few data are available regarding use of the hepatitis A vaccine in children under two years of age. The present study was conducted to test the safety and immunogenicity of inactivated hepatitis A vaccine administered to infants, and to evaluate the correlation between mother and infant anti-HAV antibodies. A total of sixty healthy children, two months of age, were enrolled in this study and immunized with 360 EU of inactivated hepatitis A vaccine (Havrix) according to the two, four and six months of age schedule. Blood sampling was performed prior to the first vaccination and one month after the third vaccination at seven months. Venipuncture was also done on mother on admission. The reactogenicity was expressed as the percentage of reported local and systemic reactions. The most common side effects were erythema on the injection site and fever. Infants with passively transferred maternal anti-HAV antibodies had a reduced anti-HAV GMT after vaccination. On admission, only one infant and his mother were seronegative and seroconversion was only detected in this infant. One month after the third dose seven infants (12.3%) were found to be seronegative. The infant without passively acquired maternal anti-HAV had the protective levels with a GMT of 3176 mIU/ml one month following the third dose. There was a significant positive correlation between the titers of mother and infant anti-HAV antibodies (n = 0.96, p < 0.001) on admission. Hepatitis A vaccine showed no immunogenicity in infants with presence of maternal antibodies. Hepatitis A vaccine is safe but it should be used after the disappearance of maternal antibodies.
Keywords: hepatitis A; vaccine; immunogenicity; side effects; infant